IMPEACHMENT PRESIDEN DAN WAKIL PRESIDEN DALAM SISTEM PRESIDENSIL PADA MASA SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR 1945 - Harry Surya Putra; Dodi Haryono; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Impeachment is a process of charges filed by the legislative branch of a government againsta civilian official. Legally the term impeachment is applied only to charges. In common usage, itincludes trials of defendants conducted by the higher branch of the legislature.This research will examine the main issues according to the scope and identification ofproblems through a normative juridical approach. Based on normative research methods, the datasources used in this research are secondary data sources which consist of 3 legal materials,namely: primary legal materials, secondary legal materials, and tertiary legal materials. Datacollected from literature studies.After the Amendment to the 1945 Constitution, the mechanism for dismissing the Presidentin Indonesia is far more complicated than before. Starting from the institutions involved and theprocess that must be passed is very different from before the 1945 Constitution was changed.Under normal circumstances, it is very difficult to remove or impeach the President and/or VicePresident. Whereas it is true that the procedure for dismissing the President and/or Vice Presidentduring their term of office has been provided for in the 1945 Constitution. It's just that to be able todo so requires a political and legal process that is quite long and tortuous. From the point of viewof the involvement of state organs and the regulation of the impeachment mechanism in the 1945Constitution, there is still room for struggle between politics and law. Given that the position ofauthority to dismiss the President and/or Vice President rests with the MPR but involves theConstitutional Court in it.Keywords: Impeachment - President and Vice President - Presidency - Amendment to the 1945Constitution